2000
DOI: 10.1007/s002230010038
|View full text |Cite
|
Sign up to set email alerts
|

Association of Methylenetetrahydrofolate Reductase (MTHFR) Polymorphism with Bone Mineral Density in Postmenopausal Japanese Women

Abstract: The pathogenesis of osteoporosis is controlled by genetic and environmental factors. Considering the high prevalence of osteoporosis in homocystinuria, abnormal homocysteine metabolism would contribute to the pathogenesis of osteoporosis. It is known that the polymorphism of methylenetetrahydrofolate reductase (MTHFR), the enzyme catalyzing the reduction of 5, 10-methylenetetrahydrofolate to 5-methyltetrahydrofolate, correlates with hyperhomocysteinemia. In this study, we examined the association of this polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
4
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(68 citation statements)
references
References 36 publications
(37 reference statements)
6
57
4
1
Order By: Relevance
“…Based on our results, an increase from 10 to 15 mmol/L would only cause a marginal increase in DPD of approximately 1.5 pmol/mmol. Similar results were found in all other studies reported (21)(22)(23). In view of the discrepancy between our results and the clinical data, it can be speculated that the stimulation of bone matrix degradation by Hcy is of limited clinical relevance and that use of the currently available bone turnover markers is not appropriate for monitoring the biochemical effects of Hcy or B-vitamin deficiencies on bone metabolism.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Based on our results, an increase from 10 to 15 mmol/L would only cause a marginal increase in DPD of approximately 1.5 pmol/mmol. Similar results were found in all other studies reported (21)(22)(23). In view of the discrepancy between our results and the clinical data, it can be speculated that the stimulation of bone matrix degradation by Hcy is of limited clinical relevance and that use of the currently available bone turnover markers is not appropriate for monitoring the biochemical effects of Hcy or B-vitamin deficiencies on bone metabolism.…”
Section: Discussionsupporting
confidence: 66%
“…Bode et al reported a relation with comparable strength between Hcy and collagen I C-terminal cross-links, another well-established bone resorption marker, in patients with coronary artery disease (21). Miyao et al found higher DPD levels in 57 subjects with a homozygous MTHFR C677T genotype, which is known to be associated with higher Hcy levels (22). Unfortunately, they did not measure Hcy, which limits the comparability with our results.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Epidemiological studies investigating the relationship between the MTHFR 677C T polymorphism and bone health add further evidence to support the view that impaired folate metabolism (and the related phenotypes of elevated homocysteine and lower folate concentrations (19,20) ) may be implicated in adverse outcomes (Table 3) (39,(47)(48)(49)(50)(51)(52)(53) . Convincingly evidence from a recent meta-analysis of twenty studies (3525 cases and 17 909 controls) found that the 677C T polymorphism was associated with BMD at all measured sites, and with a 23 % increased risk for all fractures in individuals with the MTHFR 677TT genotype compared with those with the CT or CC genotypes (13) .…”
Section: Genetic Evidencementioning
confidence: 91%
“…A point mutation in the MTHFR gene (C677T), which induces a substitution of valine for alanine, is a common variant, which is associated with reduced enzyme activity and with increased homocysteine levels. Some studies reported this polymorphism to be associated with either an increased risk of osteoporotic fractures [9,10] or lower BMD [11][12][13][14]. However, other studies fail to confirm this association.…”
Section: Introductionmentioning
confidence: 99%